Pembuatan Lilin Aromaterapi Untuk Meningkatkan Kreativitas Siswa di MAs Al Wasliyah 29 Kota Binjai - Dedy Sofyanto Simanjuntak; Eva Fadillah; Surya Sevi Wijayanna; Pratiwi Putri Lestari; Tasya Bahri; Zaikhan Asyam; Dewi Murniati (Jurnal Pengabdian Ilmu Kesehatan, 2024)
The method of treatment with the medium of odors (aromas) derived from certain plants is called aromatherapy. One of the applications of aromatherapy is by using aromatherapy candles which, if burned, will produce an aroma that can provide a therapeutic effect for humans. In addition, aromatherapy candles can also function as decorators, insect repellents, and fragrances. This community service activity aims to improve the skills of high school students in the field of entrepreneurship through the manufacture of aromatherapy candles. The activity was held on March 2, 2024 at the Al Washliyah Private Madrasah School 29 Binjai City, North Sumatra with a total of 25 participants. The activity consists of several stages, starting from the preparation stage, socialization activities, candle making techniques and product marketing strategies. Students are also provided with an understanding of the benefits of aromatherapy candles for health and relaxation. The results of this activity show that students are able to produce aroma therapy candles with good quality, improve students' practical skills and increase entrepreneurial spirit. This activity is expected to be an inspiration for other schools for the development of entrepreneurship programs.